PROMOSI SEBAGAI SALAH SATU UPAYA DALAM PEMASARAN PARIWISATA - Widoyono Widoyono (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Surakarta, 2006)
Tourism is one of the sources of regional government revenue. It needs to be managingprofessionally. Promotion is one of the elements of marketing mix that play a significant role inattracting domestic and international tourist. Promotion in tourism needs a marketing institution, itcould be government or private institution (tourism bureau/BPW) Tourism bureau with governmentinstitution have to build tourism image in the society. Also, they have to be able to control the marketand understand what customer needs and wants.